2020
DOI: 10.3390/bs10070113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Existential Thinking through Death Education: A Qualitative Study among High School Students

Abstract: The censorship of death-related issues is widespread in contemporary Western culture because the boundary between death and life is substantially managed in medical areas. In the context of Italian educational initiatives, to remove this limitation, 215 high school students in Southern Italy were educated on death through conventional and informal lessons. The students answered a questionnaire with open questions to survey their emotional and reflective experiences. Their answers were qualitatively, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
3
14
0
Order By: Relevance
“…They considered these encounters to be very meaningful experiences. The professionals working in this specific healthcare field are able to provide a unique point of view on the topic of death, but they were not regarded as omniscient or omnipotent, rather, the teachers and students perceived them as ordinary human beings, thus dispelling the aura of mystery and terror linked to death-related themes [ 40 , 63 , 64 , 65 , 66 , 67 ]. However, based on TMT and their DTA hypothesis, it is also possible that the language and coping skills learned through this program might serve to strengthen the aura of mystery surrounding death.…”
Section: Discussionmentioning
confidence: 99%
“…They considered these encounters to be very meaningful experiences. The professionals working in this specific healthcare field are able to provide a unique point of view on the topic of death, but they were not regarded as omniscient or omnipotent, rather, the teachers and students perceived them as ordinary human beings, thus dispelling the aura of mystery and terror linked to death-related themes [ 40 , 63 , 64 , 65 , 66 , 67 ]. However, based on TMT and their DTA hypothesis, it is also possible that the language and coping skills learned through this program might serve to strengthen the aura of mystery surrounding death.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in countries where students have low or moderate religiosity (e.g., Austria, Italy, Israel) fostering profound contemplation of religious themes (death, the afterlife, spirituality, etc.) may facilitate the reduction of potentially deleterious death anxiety ( Testoni et al, 2020a ). Relatedly, to support diversity and a multicultural perspective, students should be given a comparative overview of death and dying in different religions ( McClatchey and King, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The term death education (DeEd) refers to a set of activities aimed at facilitating the understanding and acceptance of death within a postmodern and secularized cultural context in which this theme is censored and considered taboo, and death is confined to the hospital environment [ 9 , 10 , 11 ]. These cultural transformations have produced the need to resume dialogue and reflect on death and related concerns since the avoidance of this topic, especially in Western societies, has become very common [ 12 , 13 , 14 ]. DeEd responds to this need, as well as the need to promote reflections on existential issues, and it leads to the management of emotional difficulties related to loss, subsequently reaching a greater sense of control over the representations of death and the anxiety related to it [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…DeEd responds to this need, as well as the need to promote reflections on existential issues, and it leads to the management of emotional difficulties related to loss, subsequently reaching a greater sense of control over the representations of death and the anxiety related to it [ 14 , 15 , 16 ]. DeEd can be achieved at different levels of prevention: primary, secondary and tertiary [ 11 , 13 , 17 , 18 ]. DeEd as primary prevention, on which the study reported in this article is focused, is implemented in situations where there is no recent experience of death but the topic is addressed in a preventive way, focusing on sharing one’s emotional experiences and building an appropriate and shared language [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation